2016
DOI: 10.1364/boe.7.004472
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz identification and quantification of neurotransmitter and neurotrophy mixture

Abstract: Terahertz spectroscopy has been widely used for investigating the fingerprint spectrum of different substances. For cancerous tissues, the greatest difficulty is the absorption peaks of various substances contained in tissues overlap with each other, which are hard to identify and quantitative analyze. As a result, it is very hard to measure the presence of cancer cell and then to diagnose accurately. In this paper, we select three typical neurotransmitters (γ-aminobutyric acid, L-glutamic acid, dopamine hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…They found that the formation of a GABA-BA cocrystal under slow solvent evaporation is affected by the pH value of the aqueous solution. Peng et al 22 researched two typical metabolites and three typical neurotransmitters, including GABA, from 0.9 to 4.5 THz by FTIR and successfully identied the components and proportions of a mixture consisting of neurotransmitters and neurotrophic substances. These works provide useful characteristics of GABA in the THz region and the tentative assignments of its modes.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the formation of a GABA-BA cocrystal under slow solvent evaporation is affected by the pH value of the aqueous solution. Peng et al 22 researched two typical metabolites and three typical neurotransmitters, including GABA, from 0.9 to 4.5 THz by FTIR and successfully identied the components and proportions of a mixture consisting of neurotransmitters and neurotrophic substances. These works provide useful characteristics of GABA in the THz region and the tentative assignments of its modes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in terahertz (THz, 0.1-10 THz) biomedical applications have garnered much interest in label-free research, owing to its unique spectral advantages [14][15][16][17]. THz photon energy meshes well with the energy levels of low-frequency molecular motions including rotation, vibration, and relative translation of the molecular skeleton, and particularly the hydrogen bonds between biomolecules and water [18].…”
Section: Introductionmentioning
confidence: 99%
“…A THz time-domain spectroscopy (THz-TDS) system was used 15 . In our experiments, 800 nm femtosecond laser characterized by pulse duration of 100 fs, repetition rate of 76 MHz, and average power of 150 mW was used.…”
Section: Methodsmentioning
confidence: 99%
“…Pump beam modulated by optical chopper was focused on a Gallium Arsenide (GaAs) and then emitted THz wave. The diverging THz beam was collected and focused by paraboloidal mirrors to pass though biological samples, and then the probe beam was used to detect THz wave with samples’ physical properties by photoconductive antennas( ) 15 17 . For our experimental system, the effective bandwidth for the measured signals is from 0.2 to 2.5 THz, the spectrum resolution is better than 15 GHz, signal to noise radio (SNR) is larger than 1000:1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation